WAYS TO SOLVE THE PROBLEM OF GAS-FLAME SPRAYING OF GLASS-ENAMEL COATINGS - Лопата, Віталій; Solovuch, Evgeny; Katerinich, Stanislav; Solovykh, Andrey (Problems of Friction and Wear, 2023)
Based on the analysis of the gas-dynamic model of two-phase flow in thermospray plants, the temperature of gas and particles was estimated, as well as the analysis of the heat exchange process in the system "extended flare-powder particles with low thermal conductivity", the possibility of spraying enamels by gas-flame method An analytical assessment of the thermal state of enamel particles in the torch and at the time of contact with the substrate is given. The values ​​of glass enamel particle and gas phase temperatures along the torch axis are theoretically determined. It is established that glass enamel particles cannot be softened in the flame of known thermal sprays due to the short length of the high-temperature zone of the torch. Theoretical analysis of the heat transfer process in the system "flare-particles of powder with low thermal conductivity" (for example, powders of glass enamels) showed that to soften them it is necessary to increase the duration of the powder in the flare. A method of gas-flame spraying with an elongated torch based on the formation of a secondary torch due to the use of the effect of combustion with separation is developed. Analytical evaluation of the thermal state of enamel particles in the torch torch and at the time of contact with the base showed the possibility of spraying powders of materials with low thermal conductivity by the gas-flame method by increasing the length of the torch / To increase the length of the torch, it is proposed to form a secondary torch at a distance from the nozzle of the thermospray and theoretically determined the distance of formation of the secondary torch.